Species of the bee genus Centris Fabricius, 1804 described by Heinrich Friese (Hymenoptera: Apidae) - Vivallo, Felipe (Zootaxa, 2020)
Primary types of Centris bees described by the German melittologist Heinrich Friese were studied. To stabilize the application of some names, lectotypes were designated for C. agilis abdominalis, C. americana bicincta, C. atriventris rubripes, C. bakeri, C. birkmannii, C. breviceps, C. bucephala, C. buchwaldi, C. burgdorfi paraguayensis, C. chilensis neoqueenensis, C. collaris fluviatilis, C. costaricensis erubescens, C. flavothoracica, C. labrosa, C. labrosa simplex, C. lateritia, C. lutea, C. metathoracica, C. mexicana albiceps, C. mixta, C. mocsaryi, C. muralis melanopus, C. nigripes, C. pauloensis, and C. versicolor rufiventris. Centris agilis abdominalis and C. labrosa simplex were revalidated from the synonymy of C. agilis Smith and C. analis (Fabricius), respectively, raising both varieties at species level. Centris fulvicollis is removed from C. (Ptilotopus) and transferred to C. (Melanocentris), transforming the former subgenus in a natural group. Centris fusciventris atriceps is proposed as n. syn. of C. mocsaryi, C. flavifrons rufescens as n. syn. of C. flavifrons (Fabricius), and C. xanthocnemis ardesiaca as n. syn. of C. xanthocnemis (Perty). Centris femoralis is withdrawn from the synonymy of C. lutea and proposed as n. syn. of C. rufipes. Taxonomic notes and comments of the remaining species described by Friese are also provided.